Dry weight loss and nutrient changes in decomposing leaf litter of Tectona grandis Linn.f. and Dalbergia sissoo Roxb. plantations raised on sodic and normal soil - Parihar, A.K.S.; Rana, B.S.; Bharti, D.K. (Indian Journal of Agroforestry, 2020)
Decomposition of leaf litter is an important process in the biogeochemical cycle and a major source of nutrients in forest ecosystems. As leaves are broken down by insect and microbial decomposers, organically-bound nutrients are released as free ions to the soil solution which are then available for uptake by plants. This paper deals with the leaf-litter decomposition of two important northern Indian timber species viz., Tectona grandis Linn.f. (teak) and Dalbergia sissoo Roxb. (shisham) were studied from May 2008 to April 2009 at two different sites in Faizabad district of eastern Uttar Pradesh. The site 1 (S1) located at Baraipara, near Kumarganj had normal soil and the site 2 (S2) near campus of N. D. University of Agriculture and Technology, Kumarganj had sodic character. The entire area falls in the tropical sub-humid region of Indo-gangetic plain. The leaf litter mass of both the species decreased during decomposition over 12 month period. D. sissoo with high nitrogen content exhibited relatively faster dry weight loss (75.8-80.8%) than that of T grandis (51.5-57.9%). Leaf litter of D. sissoo decomposed more rapidly, while T. grandis took longer time for complete decomposition. T. grandis at S2site (soil pH: 8.79-9.55) showed relatively slower rate of decomposition than S1 site. At the end of the annual cycle, D. sissoo leaf litter showed much lower N concentration (0.18-0.39%; S1 vs S2) than that of T. grandis (0.46-0.56%; S1 vs S2). Similar pattern was also discernible in case of P and K, although N assumed relatively faster release. It may be concluded that greater annual dry weight loss in leaf litter and nutrient release under normal soil condition than that of sodic soil condition reflects favourable soil character and rich soil microflora of the former under same set of the other environmental conditions.